Penguatan ketahanan moral siswa melalui program pembiasaan keagamaan di sekolah Boarding School - Widiyanto, Irfan Haris; Mustofa, Triono Ali (Idarah Tarbawiyah: Journal of Management in Islamic Education, 2026)
The advancement of globalization and digitalization has heightened students’ moral vulnerability through exposure to digital media, peer pressure, and weak self-control, thereby requiring education to strengthen moral resilience as a foundation for character formation, particularly within the intensive and controlled environment of boarding schools. This study aims to examine the strengthening of students’ moral resilience through religious habituation programs at SMP Ahmad Dahlan Sukoharjo as a boarding school. A qualitative approach with a descriptive case study design was employed. Data were collected from teachers, boarding school administrators, and students through participatory observation, in-depth interviews, and documentation, and were analyzed thematically while ensuring data validity through source and technique triangulation. The findings indicate that religious habituation programs such as congregational prayers, Qur’an recitation, short religious sermons, and nightly reflection play a significant role in strengthening students’ moral resilience. Moral resilience is reflected in the strength of faith, self-control, and consistency in practicing moral values amid the challenges of the global and digital era. Support from teacher role modeling, intensive mentoring, environmental management, and educational sanctions fosters the development of stable and sustainable internal moral awareness. Abstrak Perkembangan globalisasi dan digitalisasi meningkatkan kerentanan moral siswa melalui paparan media digital, tekanan pergaulan sebaya, dan lemahnya kontrol diri, sehingga pendidikan perlu memperkuat ketahanan moral sebagai fondasi pembentukan karakter, khususnya dalam lingkungan sekolah boarding school yang intensif dan terkontrol. Penelitian ini bertujuan mengkaji penguatan ketahanan moral siswa melalui program pembiasaan keagamaan di SMP Ahmad Dahlan Sukoharjo sebagai sekolah boarding school. Penelitian menggunakan pendekatan kualitatif dengan desain studi kasus deskriptif. Data diperoleh dari guru, pengelola boarding school, dan siswa melalui observasi partisipatif, wawancara mendalam, dan dokumentasi, kemudian dianalisis secara tematik dengan menjaga keabsahan data melalui triangulasi sumber dan teknik. Hasil penelitian menunjukkan bahwa program pembiasaan keagamaan seperti shalat berjamaah, tadarus Al-Qur’an, muhadharah, dan refleksi malam berperan signifikan dalam membangun ketahanan moral siswa. Ketahanan moral tercermin dalam kekuatan akidah, kemampuan mengendalikan perilaku, serta konsistensi menjalankan nilai moral di tengah tantangan era global dan digital. Dukungan keteladanan guru, pendampingan intensif, pengelolaan lingkungan, dan sanksi edukatif mendorong terbentuknya kesadaran moral internal yang stabil dan berkelanjutan.